An ultra-sensitive dual-responsive aptasensor with combination of liquid crystal and intercalating dye molecules: A food toxin case study. (1st July 2022) - Khoshbin, Zahra; Abnous, Khalil; Taghdisi, Seyed Mohammad; Verdian, Asma; Sameiyan, Elham; Ramezani, Mohammad; Alibolandi, Mona
Highlights: A dual-response aptasensor was developed for detection of OTA. OTA was detected with the ultra-low detection limits. The aptasensor was successfully utilized for the OTA determination in real samples. Abstract: Herein, a label-free aptasensor was designed through forming a double-stranded DNA skeleton on the glass substrate for ultrasensitive quantification of ochratoxin A (OTA) as a case study. The function fundament of the dual-responsive aptasensor was the perturbation of the vertical alignment of the liquid crystals (LCs) and intercalation of the SYBR Green I (SGI) dye molecules between the base pairs of the double-stranded DNA structure. The presence of OTA decomposed the double-stranded structure of DNA by releasing the OTA-specific aptamer from the sensing platform that induced an apparent alteration of the optical and fluorescent responses. The aptasensor specifically detected the ultra-low levels of OTA as 47.0E-9 pM (0.047 aM) and 34.0E-3 pM (34 fM) based on the polarized and fluorescent responses, respectively. The aptasensor monitored OTA in the coffee and grape drink samples. The aptasensor provides promising insight for manufacturing real-time, cost-effective, and portable sensing devices for food control usage.